المثقف الحضاري في روايات مالك حداد ( دراسة في نماذج مختارة) - ثلايجية حورية (My University, 2023)
The civilized intellectual has always been and continues to be the obsession of Algerian writers in particular and of Arabs in general, if the Algerian writers who write in French invest in it, a clear investment that we find especially in the writings of the distinguished writer Malek Haddad, whose queen unveiled the civilized intellectual who played a very important role in resolving the Algerian issue and highlighting its general features that... It appeared clearly at the level of the language, which was foreign in form and Algerian in spirit. The content and general content of these writings goes to the heart of the Algerian issue. As for the expressive language, it was French. In this particular moment, the pens stopped, the fields turned, and questions rained down on the writer Malek Haddad, to finally declare that this language, that is, the French language. In particular, it was imposed and not a choice, so he saw it because it was exile and was not a home or refuge In summary, the writer Malek Haddad was able, through his three novels: • The student and the lesson • There is no one on the flowerbed to answer • I will give you a gazelle Who drew the features of the cultural encounter through which he depicted the features of that intellectual lost between his mother civilization and the civilization that was imposed on him, which was different in culture and features, and despite the attempts of the heroes of the novels to adapt, they faced many difficulties that went beyond psychological torture and physical torture, so that the cultural intellectual won in the end and broke the barrier. Silence, by shedding light on what is silent about, thus making the Algerian issue appear realistic and treating it in a manner through which he aspires to overcome the crisis, not stop at it. Thus, Malek Haddad was able to advance his society in a very difficult time, to be the counterpart of an effective civilized Algerian intellectual ---------------------------- الملخص لطالما كان المثقف الحضاري ولازال هاجس الكتّاب الجزائرية خاصة والعرب بصفة عامة اذا استثمره الكتاب الجزائريين الذين يكتبون بالغة الفرنسية استثمار واضحا نجده خاصة في كتابات الكاتب القدير مالك حداد الذي حلول الملكة اللثام على المثقف الحضاري الذي لعب دورا بالغ الأهمية في الطير القضية الجزائرية وابراز ملامحها العامة التي ظهرت بصفة جلية على مستوى اللغة التي كانت اجنبي الشكل جزائرية الروح فالفحوي والمضمون العام لهذه الكتابات يصب في صميم القضية الجزائرية أما اللغة التعبيرية فكانت فرنسية وفي هذه القطة بالذات توقفت الأقلام ودارت المجالات وانهالت الاسئلة على الكاتب مالك حداد ليصرح في الاخير بان هذه اللغة أي اللغة الفرنسية بالذات كانت مفروضة ولم تكن اختيار لذلك رأى لأنها منفى ولم تكن مسكنا ومأوي ومجمل القول ان الكاتب مالك حداد استطاع من خلال رواياته الثلاثة المتمثلة في التلميذ والدرس ليس على رصيف الازهار من يجيب ساهبك غزالة من رسم معالم اللقاء الحضاري الذي رسم من خلاله ملامح ذلك المثقف التائه بين حضارته الام وحضارته التي فرضت عليه والتي كانت مختلفة الثقافة والملامح ورغم محاولات ابطال الروايات من التأقلم إلا انهم واجهوا الكثير من الصعاب التي تجاوزت التعذيب النفسي التعذيب الجسدية ليفوز المثقف الحضاري في الاخير ويكسر حاجز الصمت من خلال تسليطه الضوء على المسكوت عنه وبالتالي خضر القضية الجزائرية في صورة واقعية ومعالجتها معالجة يصبو من خلالها لتجاوز الازمة لا الوقوف عندها وهكذا تمكن مالك حداد من النهوض بمجتمعه في زمن جدا صعب ليكون مقابل لمثقف جزائري حضاري فاعل ------------------------------ L'intellectuel civilisé a toujours été et continue d'être l'obsession des écrivains algériens en particulier et des Arabes en général, si les écrivains algériens qui écrivent en français y investissent, un investissement évident que l'on retrouve notamment dans les écrits de l'éminent écrivain Malek. Haddad, dont la reine a dévoilé l'intellectuel civilisé qui a joué un rôle très important dans la résolution de la question algérienne et en soulignant ses traits généraux qui... Cela est apparu clairement au niveau de la langue, étrangère dans la forme et algérienne dans l'esprit. Et le contenu général de ces écrits touche au cœur de la problématique algérienne. Quant à la langue expressive, elle fut le français. A ce moment précis, les plumes se sont arrêtées, les champs ont tourné, et les questions ont plu sur l'écrivain Malek Haddad, pour finalement déclarer que cette langue, c'est-à-dire la langue française. En particulier, elle était imposée et non un choix, donc il l'a vue parce qu'elle était un exil et n'était pas un foyer ou un refuge. En résumé, l'écrivain Malek Haddad a pu, à travers ses trois romans : • L'élève et la leçon • Il n'y a personne sur le parterre de fleurs pour répondre • je te donnerai une gazelle Qui a dessiné les traits de la rencontre culturelle à travers laquelle il a décrit les traits de cet intellectuel perdu entre sa civilisation mère et la civilisation qui lui a été imposée, différente par sa culture et ses traits, et malgré les tentatives des héros des romans de s'adapter.